Involving local people in sustainable rural development and conservation: a response to the economic crisis. (1st January 2013) - Andrea, Veronika; Tsantopoulos, Georgios; Tampakis, Stilianos; Arabatzis, Garyfallos
This paper concerns the management and development of natural resources using citizens' participation in decision-making procedures. The study examines the economic growth of gateway communities in the Amvrakikos Wetlands National Park with the use of a structured questionnaire and through personal interviews. Simple random sampling was used as a method. The case study constitutes an approach used to examine local people's views concerning the various characteristics of the broader area, their living standards, as well as the sectors they wanted existing and future developments to be based upon. Through the research results, it is acknowledged that local people consider employment opportunities to be inadequate. They think that local development is based, partly, on the primary sector. Whereas, local people wish the primary sector to be enhanced along with the secondary, they want industry development and a tertiary sector, with the provision of services and tourism.